Boris Berezovsky, Varvara Myagkova, and Karina Ter-Gazarian play Gershwin, Bach, Debussy, and Khachaturian Armchair Concerts. Live broadcasts of concerts without an audience - Gershwin, George 1898-1937; Debussy, Claude 1862-1918; Bach, Johann Sebastian 1685-1750; Zaderat͡skiĭ, Vsevolod Petrovich 1891-1953; Debussy, Claude 1862-1918; Khachaturi͡an, Aram 1903-1978; Khachaturi͡an, Aram 1903-1978; Khachaturi͡an, Aram 1903-1978; Debussy, Claude 1862-1918; Debussy, Claude 1862-1918; Grieg, Edvard 1843-1907 (Moscow Philharmonic, 2020)
The 1,500 seats at Moscow's Tchaikovsky Concert Hall will remain empty today--but the grand space will resound with glorious music thanks to Boris Berezovsky, "the truest successor to the great Russian pianists" (Gramophone). Two of his brightest students, Varvara Myagkova and Karina Ter-Gazaryan (born in 2007!), join him in a kaleidoscopic recital spanning centuries and genres: from Gershwin's irresistible Rhapsody in Blue to the pure pianism of preludes by Bach and Zaderatsky, through evocative musical paintings by Debussy and Khachaturian's ballet settings, this program has everything to spark the imagination and dazzle the senses! Photo © Yuri Bogomaz
Keywords: concert; Toccatas; Rhapsodies (Music); Preludes (Music); Filmed performances; Art music; Arrangements (Music); Internet videos